2016
DOI: 10.1038/bjc.2015.436
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin fragments as potential mediators for peritoneal metastasis in advanced epithelial ovarian cancer

Abstract: Background:Peritoneal dissemination and retroperitoneal lymph node involvement are main routes for tumour spread of epithelial ovarian cancer (EOC), possibly determined by the intercellular connecting protein E-Cadherin (E-Cad) and its fragments.Methods:Tumour tissue of 105 advanced EOC patients was evaluated for protein expression of E-Cad, β-Catenin and Calpain by western blotting and immunohistochemistry. Expression patterns were compared between tumours with solely intraperitoneal (pT3c, pN0; n=41) and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Recent studies have shown that the tumor cell differentiation status (epithelial-mesenchymal transition) might influence the route of metastasis in ovarian cancer [ 38 ]. Accordingly, we could demonstrate that a 85 kDa fragment of the epithelial marker E-Cadherin is associated with intraperitoneal metastasis, whereas VEGF-C and VEGF-D are more highly expressed in tumors displaying retroperitoneal tumor spread [ 39 , 40 ]. Although CEACAM1 expression does not correlate with the mode of OvCa metastasis, its relevance for patient outcome strongly differs between both ovarian cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the tumor cell differentiation status (epithelial-mesenchymal transition) might influence the route of metastasis in ovarian cancer [ 38 ]. Accordingly, we could demonstrate that a 85 kDa fragment of the epithelial marker E-Cadherin is associated with intraperitoneal metastasis, whereas VEGF-C and VEGF-D are more highly expressed in tumors displaying retroperitoneal tumor spread [ 39 , 40 ]. Although CEACAM1 expression does not correlate with the mode of OvCa metastasis, its relevance for patient outcome strongly differs between both ovarian cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction from tumour samples and polyacrylamide gel electrophoresis were performed as described before. 15 Briefly, equal amounts of protein (20 μg) of each sample were loaded per well and equal loading was verified by immunoblotting with GAPDH antibody. As positive control, a protein extract from SKOV3 was loaded in each gel.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic variants of the E-cadherin gene were reported to be a prognostic marker to identify patients at increased risk of invasive or metastatic cancer (8). E-cadherin fragmentation was revealed to promote the progression of intraperitoneal epithelial ovarian cancer (9). However, the effects of CD44 and E-cadherin overexpression on cell proliferation, adhesion and invasion of ovarian cancer cells have remained elusive.…”
Section: Introductionmentioning
confidence: 99%